2017
DOI: 10.1523/jneurosci.1372-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Prior Learning of Relevant Nonaversive Information Is a Boundary Condition for Avoidance Memory Reconsolidation in the Rat Hippocampus

Abstract: Reactivated memories can be modified during reconsolidation, making this process a potential therapeutic target for posttraumatic stress disorder (PTSD), a mental illness characterized by the recurring avoidance of situations that evoke trauma-related fears. However, avoidance memory reconsolidation depends on a set of still loosely defined boundary conditions, limiting the translational value of basic research. In particular, the involvement of the hippocampus in fear-motivated avoidance memory reconsolidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 92 publications
3
53
0
Order By: Relevance
“…To simulate the main experimental protocol of Radiske et al (2017), we used the schema shown in Figure 2A, where each session corresponds to the respective input pattern shown in Figure 2B. The first stage is the storage of the non-related memory by the input Inr in all networks (notice that the activated neurons in this pattern do not overlap with those in the other patterns).…”
Section: Experimental Protocol and Network Input Patternsmentioning
confidence: 99%
See 4 more Smart Citations
“…To simulate the main experimental protocol of Radiske et al (2017), we used the schema shown in Figure 2A, where each session corresponds to the respective input pattern shown in Figure 2B. The first stage is the storage of the non-related memory by the input Inr in all networks (notice that the activated neurons in this pattern do not overlap with those in the other patterns).…”
Section: Experimental Protocol and Network Input Patternsmentioning
confidence: 99%
“…Specifically, it is defined by Ir = Is + (Ins -Is)f(#), where #  [#min = 0, #max = 10] -the "pattern number"is related to the duration of the nonreinforced reexposure session, and f(#) = 1 / (1 + e (#max / 2) -# ) is a function representing the ratio between input patterns Ins and Is and varies monotonically between 0 and 1 (Osan et al, 2011). To simulate a 40-second reexposure session (Radiske et al, 2017), we used # = 3.1, which corresponds to Ir closer to the aversive memory ( Figure 2B).…”
Section: Experimental Protocol and Network Input Patternsmentioning
confidence: 99%
See 3 more Smart Citations